Estimation of demand and supply of livestock feed and fodder in Rajasthan: a disaggregated analysis - CHAND, PREM; SIROHI, SMITA; SIROHI, SUNIL KUMAR; CHAHAL, VED PARKASH (The Indian Journal of Animal Sciences, 2015)
The paper estimates the district level availability and requirement of livestock feed and fodder in Rajasthan using secondary data of triennium ending 2008–09. Availability of dry fodder and concentrates were estimated using appropriate conversion ratios to different field crop production, while green fodder was estimated by applying per hectare yield to different fodder sources. The requirement was worked out by converting livestock into adult cattle units and multiplying by per unit consumption capacity. The annual availability of feed and fodder in the state was estimated at 51.54 million tonne is against the requirement of 68.61 million tonne and thereby deficit of around 25% per annum. The feed deficiency was estimated almost in all the districts except in the districts of Hanumangarh, Bikaner, Jaisalmer, Churu and Ganganagar. The eastern and south eastern districts were deficit in green fodder whereas western and southern hill districts were deficit in dry fodder. Other critical dimensions were low roughage: concentration ration (1:0.06) and high population pressure on pasture and grazing lands. The policies to develop silvi-pastoral model, creation of fodder banks/ storage facilities, strengthening extension system, developing drought resistant and high yielding variety, crop varieties with emphasis on fodder component needs priority attention.